2016
DOI: 10.1080/10245332.2016.1220120
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of iron status and other hematological parameters in preeclampsia

Abstract: Higher SF levels, despite being within normal range, were associated with PE. The incidence of thrombocytopenia was higher in preeclamptic women, however, the remaining hematological parameters were similar in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Our results that there is a hyperferritinaemia in PE are similar to other studies [23][24][25] . Raman et al 26 showed higher mean ferritin levels in pregnant women with pregnancy induced hypertension and PE, concluding that hyperferritinaemia may mask iron deficiency.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results that there is a hyperferritinaemia in PE are similar to other studies [23][24][25] . Raman et al 26 showed higher mean ferritin levels in pregnant women with pregnancy induced hypertension and PE, concluding that hyperferritinaemia may mask iron deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…Iron overload has been associated with ferroptosis involving other organ systems 5 , notably those implicated in the pathophysiology of PE 25,[33][34][35] , as well as gestational diabetes (GDM), a condition also associated with adverse birth outcomes 29,[36][37][38] . While women who have anaemia should be treated, without understanding the cause of anaemia we risk subjecting women to iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial, albeit indirect, evidence to support this hypothesis, summarized below:Numerous studies investigating the association between iron status and hypertensive disorders of pregnancy have noted that levels of circulating iron and ferritin, as well as the level of Tf saturation, are significantly higher in PE patients as compared to normotensive controls [135,136,137]. Whether or not the increased serum iron in PE is due to low circulating hepcidin levels is unclear.…”
Section: Molecular Basis For Dysregulated Iron Homeostasis In Preementioning
confidence: 99%
“…pregnant with preeclampsia compared with the control group. 37 In the study of Laila et al (2014) regarding the relationship between serum ferritin and iron parameters with preeclampsia also have the same findings as the Gutierrez-Aguirre study. 38 The mechanism of increasing ferritin levels in some of the studies above can be explained by the theory of oxidative stress.…”
Section: Discussionmentioning
confidence: 65%
“…When the tissue becomes ischemic, reactive oxygen species such as superoxide and hydrogen peroxide are produced. 34,37,38 The presentation of the placenta in preeclamptic patients shows a histologic appearance with severe vascular damage in the area of attachment of decidua cells in the infarct area, this corresponds to cell damage and detachment. Fe.…”
Section: Discussionmentioning
confidence: 99%